The Relationship Between Leg Explosive Power and Flexibility and Long Jump Ability in Squat Style - Ricardo Valentino Latuheru; Sahabuddin Sahabuddin; Muhammad Ishak (UNIVERSITAS NEGERI MAKASSAR, 2024)
This research aims to determine the relationship between leg explosive power and flexibility and long jump ability in squatting style at UPT-SPF students at SD Inpres Panaikang II/1. This research is a descriptive study with one dependent variable, namely squatting long jump ability. The sample in this study consisted of 50 students. The instruments in this study used a long jump test without a start for leg explosive power, a forward bending flexibility test for flexibility data, and a squatting long jump ability test for squatting long jump ability data. Data analysis obtained the following results: (1) There is a relationship between leg explosive power and squatting long jump ability with correction results (r) = -0.451 (P < 0.05). (2) There is a relationship between flexibility and squatting long jump ability with a corrected value (r) = -0.425 (P < 0.05). (3) There is a joint relationship between leg explosive power and flexibility and squatting long jump ability with a corrected value of (R) = 0.496 (P < 0.05) and F value = 7.652 (P value = 0.000 < 0.05).